A Traditional Chinese Medicine Plant Extract Prevents Alcohol-Induced Osteopenia - Qian, Dongyang; Zhou, Hui; Fan, Pan; Yu, Tao; Patel, Anish; O’Brien, Morgan; Wang, Zhe; Lu, Shiguang; Tong, Guoqiang; Shan, Yimin; Wang, Lei; Gao, Yuan; et al. (Frontiers in Pharmacology, 2021)
Traditional Chinese medicine (TCM) has been practiced in the treatment of bone diseases and alcoholism. Chronic excessive alcohol use results in alcohol-induced bone diseases, including osteopenia and osteoporosis, which increases fracture risk, deficient bone repair, and osteonecrosis. This preclinical study investigated the therapeutic effects of TCM herbal extracts in animal models of chronic excessive alcohol consumption-induced osteopenia. TCM herbal extracts (Jing extracts) were prepared from nine Chinese herbal medicines, a combinative herbal formula for antifatigue and immune regulation, including Astragalus, Cistanche deserticola, Dioscorea polystachya, Lycium barbarum, Epimedium, Cinnamomum cassia, Syzygium aromaticum, Angelica sinensis, and Curculigo orchioides. In this study, Balb/c male mice were orally administrated alcohol (3.2 g/kg/day) with/without TCM herbal extracts (0.125 g/kg, 0.25 g/kg, or 0.5 g/kg) by gavage. Our results showed that after 50 days of oral administration, TCM herbal extracts prevented alcohol-induced osteopenia demonstrated by u-CT bone morphological analysis in young adults and middle-aged/old Balb/c male mice. Biochemical analysis demonstrated that chronic alcohol consumption inhibits bone formation and has a neutral impact on bone resorption, suggesting that TCM herbal extracts (Jing extracts) mitigate the alcohol-induced abnormal bone metabolism in middle-aged/old male mice. Protocatechuic acid, a natural phenolic acid in Jing extracts, mitigates in vivo alcohol-induced decline of alkaline phosphatase (ALP) gene expression in the bone marrow of Balb/c male mice and in vitro ALP activity in pre-osteoblast MC3T3-E1 cells. Our study suggests that TCM herbal extracts prevent chronic excessive alcohol consumption-induced osteopenia in male mice, implying that traditional medicinal plants have the therapeutic potential of preventing alcohol-induced bone diseases.